ASSOCIATION BETWEEN SLEEP QUALITY AND DEPRESSIVE SYMPTOMATOLOGY IN PATIENTS WITH MULTIPLE SCLEROSIS - Semnic, Isidora R.; Gebauer Bukurov, Ksenija (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Sleep quality deterioration and depressive mood are common in patients with multiple sclerosis (MS). The pattern of sleep can be changed due to many psychological and physical symptoms, as well as sociodemographic characteristics occurring within MS. Aim: The study aim was to examine the frequency of changes in sleep quality, depression, anxiety and stress, in MS patients, using the following screening tools: the Pittsburgh Sleep Quality Index – PSQI test and the Depression, Anxiety, and Stress Scale – DASS test, whilst taking into account socio-demographic features, disease duration, as well as the score on the Expanded Disability Status Scale – EDSS score. The aim was also to determine the association between the global PSQI score and socio-demographic characteristics, the EDSS score and illness duration, as well as to examine the relation between the global PSQI score and the DASS subscores. Materials and methods: The study involved 53 patients, aged 19 – 56, with relapsing-remitting MS, treated with interferon beta. The PSQI index, which evaluates sleep quality, the DASS scale for assessing depression, anxiety, and stress, as well as the EDSS score, which evaluates the severity of the disease, were used. The data was interpreted in the SPSS (Statistical Package for the Social Sciences) statistical program (standard statistical methods, bivariate correlation, linear regression). Results: Sleep quality disorder was present in 44.4% of the examined sample. A positive correlation between the PSQI score and the DASS scale subcscores was established, and linear bivariate regression showed depression (p = 0.001), anxiety (p < 0.001), and stress (p <0.001) to be predictors of the deterioration of sleep quality. A statistically significant correlation between the age of the subjects and sleep quality was determined (p = 0.047). Conclusion: In MS patients with the relapsing-remitting form of the disease, who are treated with immunomodulatory therapy, a significant association between sleep quality and depression, anxiety, and stress, was detected. Of the sociodemographic characteristics, the only established association was the relation between age structure and sleep quality, measured with the PSQI index.